Physical fatigue assessment for intrastate bus driver - Zulkifli Jasmin, Zahir Fikri Bin; Azlis-Sani, Jalil; Md Rohani, Munzilah; Abd Hamid, Nor Aziati; Sabri, S. M.; Ismail, S. M.; Ahmad Tajedi, Noor Aqilah; Abd Aziz, Roseni; Md Zein, Raemy (Asian Research Publishing Network, 2016)
Fatigue is considered a psychological or mental fatigue type characterized by subjective feelings of a disinclination to continue driving, drowsiness, fatigue, and deduction motivation. Bus drivers in Malaysia have been facing physical fatigue from driving for many years. Therefore, investigating the psychophysiological factor that related to fatigue could improve understanding and management for fatigue in the transport industry. Physical factors are divided by two parts that is upper and lower body. The objective of this study is to identify the cause, determine the level and analyze the physical fatigue on bus driver. There were two methods applied in this study, which were Modified Nordic Questionnaires that represent subjective measurement and surface Electromyography (sEMG) the objective measurement. Results from sEMG showed neck and upper back muscle groups leads to fatigue as the muscle is running out of energy based from the graph. Through the sEMG data, it can determine the level of physical fatigue on bus driver and analyzed the physical fatigue. Findings of this study from the questionnaire data analysis using the Statistical Package Social Science software, it is proved that physical fatigue really occurred to the intrastate bus driver. Results also showed significant correlation relationship between physical and mental.